Lived Experiences of Middle Level Leaders in the Nepali Institutional Schools - Kafle, Narayan Prasad (Journal of Education and Research, 2013)
This paper explicates the contextually embedded meaning of being middle level leaders in Nepali institutional schools. Using in-depth interview and protocol writing as the means of data generation, this article unearths the experience of three middle level leaders. Distributed leadership theory (Spillane, 2006) and its constructs of leadership plus aspect and leadership practice aspect provide the theoretical lens to unveil the myths and realities of being middle level leaders. All three participants shared their common acknowledgement about the significance and sensitivity of middle level leadership roles for school administration and effectiveness. Individual essence of being a middle level leader was contingent to the very context where they worked. Their feelings of being relegated, marginalized, helplessness or of high exhilaration were subjects to the contextual reality. DOI: http://dx.doi.org/10.3126/jer.v3i2.8398Journal of Education and Research August 2013, Vol. 3, No. 2, pp. 59-78